Do Flashcards Improve Biology Learning? A Systematic Review of Cognitive Learning Outcomes - Ponasari Baron Mutiara Kenya; Made Duananda Kartika Degeng; Fikri Aulia (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
Biology learning is often considered challenging due to its complex concepts, abstract processes, and numerous terms, which often result in low cognitive learning outcomes among students. Many students rely on passive learning strategies that are insufficient to support meaningful understanding and long-term retention. Consequently, there is a need for effective, evidence-based instructional media that can actively engage students and improve cognitive achievement in biology learning. This systematic literature review aims to examine the effectiveness of flash cards in improving students' cognitive learning outcomes in biology and to identify how they are used in classroom instruction. This study employs a systematic literature review to analyze empirical research articles published between 2021 and 2025 that investigate the use of flashcards in biology learning. The selected studies include experimental, quasi-experimental, and developmental research designs, mostly conducted at the secondary education level. Data were analyzed through qualitative descriptive methods by comparing the implementation of learning, learning outcomes, and cognitive impacts reported between the experimental and control groups. The results showed that flash cards consistently improved students' cognitive learning outcomes, particularly in remembering, understanding, and applying biology concepts. The experimental group that used flashcards achieved higher posttest scores and greater learning gains than the control group that used conventional learning methods. Flashcards were most effective when integrated into active learning activities, supported by visual representations, and used to facilitate repeated retrieval of biological knowledge.